The prevalence and clinical features associated of hypothyroidism among Thai systemic sclerosis patients - Yathao Paolee (Nature Portfolio, 2021)
Abstract Thyroid disease, particularly hypothyroidism, has been reported in systemic sclerosis (SSc). Some clinical features of SSc can also present in hypothyroidism. Our aims were to determine the prevalence of, and describe clinical features associated with, hypothyroidism in SSc patients. We conducted a historical cohort study of adult SSc patients who underwent screening thyroid function tests at the Scleroderma Clinic, Khon Kaen University, Thailand, between 2009 and 2018. The patients who had any thyroid disorders before the onset of SSc and were diagnosed as an overlap syndrome were excluded. A total of 200 SSc were included according to sample size calculation, among whom the female to male ratio was 2:1. The majority of cases (137; 69.5%) were diffuse cutaneous SSc subset. The mean age was 55.8 ± 10.7 years and the median duration of disease 4.9 (IQR 1.6–9.9) years. Of the total, 9 had primary hypothyroidism (prevalence 4.5%; 95%CI 2.1–8.4) and 22 had subclinical hypothyroidism (prevalence 11%; 95%CI 7.0–16.2). Of the latter 22, 71% had dcSSc. Logistic regression analysis indicated that unexplained anemia was significantly associated with either subclinical hypothyroid or hypothyroidism (OR 2.74; 95% CI 1.17–6.47), whereas Raynaud’s phenomenon had a negative association (OR 0.28; 95% CI 0.11–0.66). Neither severity of skin tightness nor internal organ involvement were associated with hypothyroidism among SSc patients. Clinical-subclinical hypothyroidism is uncommon among SSc patients, it is frequently associated with anemia, and less so Raynaud’s phenomenon. Clinical-subclinical hypothyroidism should thus be considered in cases of unexplained anemia in SSc patients.